Bioactive Volatile Content of the Stem and Root of Centaurea carduiformis DC. subsp. carduiformis var. carduiformis - Ibrahim Demirtas; Ayse Sahin (Journal of Chemistry)
Several species of Centaurea, biennial (or more rarely perennial) plants which belong to the Asteraceae family, possess medicinal properties and are currently used in phytotherapy. In the present study, antiproliferative activity of hexane extract from stems and roots of Centaurea carduiformis DC. subsp. carduiformis var. carduiformis (CCS and CCR) on Vero cells (African green monkey kidney), C6 cells (Rat Brain tumor cells), and HeLa cells (human uterus carcinoma) was investigated in vitro. Antiproliferative effect of the extract was tested at 500 μg/mL and 1000 μg/mL using BrDu Cell Proliferation ELISA. The hexane extract was significantly inhibited proliferation of Vero, HeLa, and C6 cancer cell lines with absorbance values. The extract of CCS and CCR showed the highest activity against the Vero, HeLa, and C6 cell lines at 500 μg/mL and 1000 μg/mL.